2015
DOI: 10.1186/s12882-015-0142-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations of fish oil and vitamin B and E supplementation with cardiovascular outcomes and mortality in people receiving haemodialysis: a review

Abstract: BackgroundCardiovascular complications are the leading cause of mortality in patients with end-stage kidney disease. Research indicates that the Mediterranean diet is protective of cardiovascular disease in the general population. Components of this diet have been trialled in haemodialysis patients with the aim of reducing the risk of cardiovascular disease and improving associated risk factors. Components include fish, fruit and vegetables in the form of fish oil supplements and vitamin and antioxidant supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In the case of these individuals, the dialysis regimen itself requires additional coordination with the fasting schedule during R. Additionally, HD patients are at an increased risk for cardiovascular disease (CVD) partly attributed to dyslipidemia, increased inflammation, and poor nutritional status [19,20,21,22,23], and they could promote low-density lipoprotein (LDL) oxidation, endothelial injury, and the accumulation of lipids in the artery wall [24]. On the other hand, a diet approach could be beneficial to control them [24,25]. The findings from several studies in Saudi Arabia report that poor nutritional status and high prevalence of malnutrition (among HD patients) are consistent with these observations [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of these individuals, the dialysis regimen itself requires additional coordination with the fasting schedule during R. Additionally, HD patients are at an increased risk for cardiovascular disease (CVD) partly attributed to dyslipidemia, increased inflammation, and poor nutritional status [19,20,21,22,23], and they could promote low-density lipoprotein (LDL) oxidation, endothelial injury, and the accumulation of lipids in the artery wall [24]. On the other hand, a diet approach could be beneficial to control them [24,25]. The findings from several studies in Saudi Arabia report that poor nutritional status and high prevalence of malnutrition (among HD patients) are consistent with these observations [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Existing randomized controlled trials of higher dose n-3 PUFA supplementation in patients on hemodialysis have reported no significant effect on allcause mortality and arteriovenous fistula failure, but reduced risk of thrombosis in arteriovenous grafts and cardiovascular events [39e42]. None have assessed the impact of n-3 PUFA supplementation on cardiovascular mortality as the primary outcome in this population [26,27].…”
Section: Discussionmentioning
confidence: 98%
“…Antioxidants are not proven to be of survival benefit for any ailment till date. 20 Hence it can be inferred that the inclusion of antioxidants is for providing a placebo cum feel good factor. Inclusion of medicines in prescriptions that are not actually indicated or are of dubious benefit should be avoided.…”
Section: Discussionmentioning
confidence: 99%